Behavioral Effects of Employee Stock Ownership: French Case - Ahmed, Dalenda Ben (Asian Journal of Empirical Research, 2020)
The present work scrutinizes the effects of the employee-stock-ownership practice on the organizational performance through its impact on the employees’ behavior at work. This study sheds light on the role and contribution of this practice to the corporate governance mechanisms. This article uses a sample of 30 French-listed companies during the period 2008-2012. The empirical approach is a "regression of panel data". The results indicate the shrinkage of absenteeism and turnover of the employee shareholders. This work is to show that the ESO and the delegation of power are not only responsible for the improvement of the financial performances but also for a more effective management of human resources: lower absenteeism and turnover.